A pattern of images on advanced scientific technologies (II): Examining the relationships between image, familiarity, and personality - HIROOKA, Shuichi; MATSUURA, Hitoshi; MURAKAMI, Takashi; WAKABAYASHI, Mitsuru (Japanese Journal of Administrative Science, 1990)
The purpose of this study is to examin the relationships between the following three data sets:(1) evaluative ratings (5-point scale) on 10 most advancedscientific technologies (i. e., artificial intelligence, bio-technology, nuclear power generation, space technology, linear motor car, tube baby, 5th generation computer, super conductivity, organ transplant, and high-speed reactor), (2) familiarity ratings (5-point scale) on the same technologies, and (3) ratings on the subject's own personality (Y-G Personality Inventory). A hierarchical component analysis technique for the multiset data (Murakami, 1989) was applied. Three first order components for the image data sets were interpreted as indicating dangerous and harmful, useful and development, and personally beneficial dimensions, while the two first order components for the familiarity, as industrial technology and medical technology. Second order components showed several intersting relationships between image and familiarity which were found to be specific to particular scientific technologies. For example, industrial technologies high in the familiarity demension tended to have an image of usefulness and development.